2009
DOI: 10.1111/j.1365-2141.2008.07531.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐associated difference in gene expression of paediatric acute myelomonocytic lineage leukaemia (FAB M4 and M5 subtypes) and its correlation with prognosis

Abstract: Acute myeloid leukaemia, French-American-British M4 and M5 subtypes (AML-M4/M5) is frequently associated with MLL gene rearrangement and its incidence is relatively high among infants. Clinically, paediatric AML-M4/M5 has been considered as an intermediate or undefined prognostic group. In this study, we analysed gene expression of 40 paediatric AML-M4/M5 patients excluding inv(16) and t(8;21) patients, and found striking differences among the patients in an age-associated manner. In particular, most of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 47 publications
1
9
0
1
Order By: Relevance
“…The signal values were normalized so that the mean in each experiment was set at 100 to adjust for minor differences between the experiments. Statistical analyses and fold change calculations were performed using expression values that were logtransformed after addition of 10 to reduce adverse effects caused by noise at low expression levels (Ichikawa et al, 2006;Jo et al, 2009). To identify differentially expressed probe sets between NUP98-NSD1-positive and -negative patients, Pvalues in Student's t-test and fold change values were used.…”
Section: Microarray Analysismentioning
confidence: 99%
“…The signal values were normalized so that the mean in each experiment was set at 100 to adjust for minor differences between the experiments. Statistical analyses and fold change calculations were performed using expression values that were logtransformed after addition of 10 to reduce adverse effects caused by noise at low expression levels (Ichikawa et al, 2006;Jo et al, 2009). To identify differentially expressed probe sets between NUP98-NSD1-positive and -negative patients, Pvalues in Student's t-test and fold change values were used.…”
Section: Microarray Analysismentioning
confidence: 99%
“…Therefore, an altered expression of ZNF521 may be an important cofactor contributing to hematopoietic cell transformation. Recently, high expression of ZNF521 has been observed in pediatric AML, particularly in those cases carrying MLL gene rearrangements [20, 21]; however the role of ZNF521 in MLL -rearranged AML is currently unknown. In this study, we examined the role of ZNF521 in MLL -rearranged AML cell lines and primary ex vivo MLL-AF9 -expressing cells and showed that depletion of ZNF521 impaired AML progression by inducing myeloid differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, investigation of pediatric AML patients with FLT3-mutations allowed the identification of a RUNX3 to ATRX expression ratio that correlated with outcome, irrespective of the FLT3 mutation status, 34 and a small study in pediatric acute myelomonocytic leukemia (characterized by FAB M4/M5 morphology) revealed age-associated gene expression differences that might be associated with outcome. 35 Thus, like in adult AML, results of pediatric studies hold great promise that GEP-based prognostication is feasible.…”
Section: Gep In Pediatric Amlmentioning
confidence: 99%